2015
DOI: 10.5472/mmjoa.2803.01
|View full text |Cite
|
Sign up to set email alerts
|

Determination of spatial proximity between the N-terminus and cocaine binding site of the dopamine transporter by FRET.

Abstract: Objective: The dopamine transporter (DAT) mediates uptake of dopamine from the synaptic cleft and provides rapid termination of neurotransmission. It is the site of action for different drugs of abuse, including cocaine and amphetamine. Serine 7 and 12 at the N-terminus were found to be critical residues in phosphorylation. Here, we addressed spatial proximity site relationship of N-terminal extension with respect to cocaine binding in wild type and Ser7/12Asp and Ser7/12Ala mutants. Materials and Methods:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…These results, in accordance with the model based on the crystal structure of LeuT, verify the role of residues upstream to position 55 in activation of DAT (Beuming et al, 2008). In an earlier study, we reported that there is no FRET interaction between the extreme N-terminus or its phosphomimicking mutants and the cocaine-analog binding site (Orun and Tiber, 2015). The lack of FRET for the N-term position 1, together with the current finding for position 55, suggests that the very end of DAT has an extended structure, further away from ligand binding sites.…”
Section: Discussionsupporting
confidence: 90%
“…These results, in accordance with the model based on the crystal structure of LeuT, verify the role of residues upstream to position 55 in activation of DAT (Beuming et al, 2008). In an earlier study, we reported that there is no FRET interaction between the extreme N-terminus or its phosphomimicking mutants and the cocaine-analog binding site (Orun and Tiber, 2015). The lack of FRET for the N-term position 1, together with the current finding for position 55, suggests that the very end of DAT has an extended structure, further away from ligand binding sites.…”
Section: Discussionsupporting
confidence: 90%